Pengaruh Suku Bunga Kredit Terhadap Penyaluran Kredit Pada PT Bank Mandiri (Persero) Tbk - Reinaldi Butarbutar; Jonni Hamonangan Silaen (Jurnal Budgeting, 2025)
This research is titled "The Effect of Credit Interest Rates on Credit Distribution at PT Bank Mandiri (Persero) Tbk." The purpose of this study is to determine the effect of interest rates on credit distribution at PT Bank Mandiri (Persero) Tbk for the 2020–2024 period. The type of data used is the financial statements of PT Bank Mandiri (Persero) Tbk, obtained through documentation techniques. The data processing method used is simple linear regression. The results show that the interest rate has a negative and significant effect on the amount of credit distributed by PT Bank Mandiri (Persero) Tbk during the study period. This is evidenced by the correlation coefficient of -0.79 and a coefficient of determination of 62.41%.